2019
DOI: 10.1016/j.neuron.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Cellular Clearance Is Mediated by the SNARE Protein ykt6 and Disrupted by α-Synuclein

Abstract: Highlights d ykt6 responds to lysosomal stress by enhancing hydrolase trafficking d a-Synuclein impedes the lysosomal stress response by blocking ykt6 in patient neurons d Reducing the farnesylation of ykt6 enhances hydrolase trafficking and lysosomal function d Farnesyltransferase inhibitors activate ykt6 and lysosomes in patient neurons and mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 77 publications
4
59
0
1
Order By: Relevance
“…A second group found that αS impairs trafficking of hydrolases to lysosomes by inhibiting the function of the SNARE protein ykt6 53 . Ykt6 is regulated by both palmitoylation and farnesylation in a unique manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second group found that αS impairs trafficking of hydrolases to lysosomes by inhibiting the function of the SNARE protein ykt6 53 . Ykt6 is regulated by both palmitoylation and farnesylation in a unique manner.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent palmitoylation of an adjacent cysteine then permits adoption of an “open” conformation, membrane association, and SNARE activity 55 . Farnesyltransferase inhibitors restored ykt6‐dependent hydrolase trafficking 53 . The influence of palmitoylation on ykt6 was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…GluCer-induced aSyn forms have also been directly associated with endogenous neurotoxicity, as well as decreased neuronal viability upon endocytosis from healthy DAergic neurons ( Zunke et al, 2018 ). An equally important aspect of the aSyn–GCase interaction is that increased aSyn levels can per se impair lysosomal GCase activity via improper enzyme maturation and trafficking, an effect that also disrupts other lysosomal enzymes ( Mazzulli et al, 2016a ; Cuddy et al, 2019 ). Specifically, aSyn disrupts the association between the SNARE protein ykt6, implicated in ER–Golgi trafficking, and membranes, validated in iPSC-derived DAergic neurons from SNCA triplication- or A53T aSyn PD patients ( Cuddy et al, 2019 ).…”
Section: Lysosomal Dysfunction and Alpha-synuclein Linked By Glucocermentioning
confidence: 99%
“…An equally important aspect of the aSyn–GCase interaction is that increased aSyn levels can per se impair lysosomal GCase activity via improper enzyme maturation and trafficking, an effect that also disrupts other lysosomal enzymes ( Mazzulli et al, 2016a ; Cuddy et al, 2019 ). Specifically, aSyn disrupts the association between the SNARE protein ykt6, implicated in ER–Golgi trafficking, and membranes, validated in iPSC-derived DAergic neurons from SNCA triplication- or A53T aSyn PD patients ( Cuddy et al, 2019 ). Further mechanistic investigations in iPSC-derived DAergic neurons have revealed that some PD-associated proteins exert an inhibitory effect on GCase activity that can, at least partly, be attributed to DA oxidation.…”
Section: Lysosomal Dysfunction and Alpha-synuclein Linked By Glucocermentioning
confidence: 99%
See 1 more Smart Citation